Show yourself: present with confidence / Nur Syaqirah Nadhilah Zulbaidi and Geraldine John Philip De Mello - Zulbaidi, Nur Syaqirah Nadhilah; John Philip De Mello, Geraldine (Akademi Pengajian Bahasa, 2021)
Skills for presentation takes up a huge space in determining a clear execution by the presenter. The purpose of this study is to edify the basics of presentation skills and to assist in the lack of confidence among students. An E-book was produced to include the basics and ways to improve presentation skills. Participants from the age of 16 to 20 years old participated in an online session and a questionnaire was answered by them which resulted in the acknowledgement on the average understanding regarding this skill and not having confidence when presenting. After the session and the distribution of the E-book, participants stated that the session added to their knowledge and was able to instill confidence in them for future presentations based on the survey that was given. Majority agreed that the session was beneficial and they acquired knowledge also knowing how to increase self confidence with body language tips and many more. In conclusion, the presentation skill is an ability that is often used in today’s environment. This study aims to assist in the skills of presenting and increasing one’s self-confidence when it involves speaking in front of a crowd and being the center of attention.